Pendampingan Aktivasi RedSeller Baru Berbasis Digital melalui Program Magang MBKM di PT Commeasure Solution Indonesia: RedDoorz Indonesia - Miftahul Abror Priambada; Rizky Dermawan (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
This community service activity was conducted through the Merdeka Belajar Kampus Merdeka (MBKM) Internship Program at RedDoorz, focusing on digital-based assistance for new RedSeller activation. Students acted as mentors supporting onboarding, application usage, and digital promotion strategies. A descriptive qualitative method was applied using observation, documentation, and thematic analysis. The results indicate that mentoring improved RedSellers’ understanding of application features, facilitated the activation process, and increased confidence in digital marketing activities. In addition, the program enhanced students’ competencies in technical skills, interpersonal communication, and mentoring management. Visual-based assistance proved effective in supporting the learning process of new RedSellers.